The Man Made of Smoke : a Novel - North, Alex, 1976- (New York : Celadon Books, 2025)
"Dan Garvie's life has been haunted by the crime he witnessed as a child--narrowly escaping an encounter with a notorious serial killer. He has dedicated his life since to becoming a criminal profiler, eager to seek justice for innocent victims. So when his father passes away under suspicious circumstances, Dan revisits his small island community, determined to uncover the truth about his death. Is it possible that the monster he remembers from his childhood nightmares has returned after all these years?"--
Keywords: Serial murderers -- Fiction; Fathers and sons -- Fiction; Fathers -- Death -- Fiction; Murder -- Investigation -- Fiction; Thrillers (Fiction)